The effects of authenticity and credibility of influencer marketing on purchase intention and brand awareness: a case study of Casa Pardal - Diaz, Laila Boavista Costa (My University, 2025)
This dissertation investigates the influence of influencer marketing’s perceived authenticity and credibility on consumer purchase intention and brand awareness, using a traditional Portuguese pastry brand, Casa Pardal, as a case study. The decision on choosing Casa Pardal lays on the fact that the owners are their own influencers. In the evolving digital landscape, consumers increasingly demand trustworthy and sincere brand representations, especially within the food sector. This study employs a quantitative methodology approach combining sentiment analysis of user-generated content on social media with a structured survey distributed to Casa Pardal's followers and customers. The sentiment analysis, applied to Facebook comments and reactions during peak engagement periods, demonstrates overwhelmingly positive emotional responses, reinforcing the significance of emotional tone in driving consumer engagement. The survey results further confirm that perceived credibility and authenticity of the brand's owners, who act as influencers, play a crucial role in enhancing brand trust and influencing purchase decisions. This research contributes to the academic understanding of digital influence by demonstrating that micro-influencers, when perceived as credible and authentic, can foster strong consumer-brand relationships and effectively increase brand visibility and purchase intention, even in traditional business contexts.
Keywords: Influencer marketing; Authenticity; Credibility; Purchase intention; Brand awareness; Sentiment analysis; Social media; Micro-influencers; Consumer behaviour; Casa Pardal